(untitled) (International journal of artificial intelligence, 2026)
This article discusses the problem of shyness among university students in English speaking classes. Many students have sufficient language knowledge and good academic potential, but they experience fear, nervousness, and lack of confidence when speaking in front of teachers and classmates. The article explains the main causes of speaking anxiety, including fear of making mistakes, low self-confidence, classroom pressure, and limited speaking practice. In addition, the article describes the negative effects of shyness on students’ academic performance, communication skills, and future professional development. Several practical and communicative teaching strategies are suggested to help students become more active, confident, and motivated speakers in university classrooms.